Subchronic Study of a White Kidney Bean (Phaseolus vulgaris) Extract with α-Amylase Inhibitory Activity. (22nd November 2019) - Qin, Guangqiu; Wang, Fang; Liang, Huili; Tang, Song; Shekh, Kamran; Wang, Yanwu; Li, Bin; Dong, Baiqing; Wen, Pingjing
Abstract : Common bean extract as a dietary supplement has received increased attention globally owing to its α -amylase inhibitory activity. The objective of this study was to evaluate the toxicity of a white kidney bean ( Phaseolus vulgaris ) extract by a repeated-dose 90-day subchronic oral toxicity study in Sprague-Dawley rats. In the subchronic toxicity study, 80 rats were orally administrated with white kidney bean extract at doses of 4, 2, and 1 g/kg body weight daily for 90 days. The results showed that the white kidney bean extract at doses up to 4 g/kg/day did not induce significant changes in body weight, organ weight, food consumption, hematology, serum biochemistry, and histopathology in rats, as compared to the control. The no-observed-adverse-effect level (NOAEL) of white kidney bean extract was determined to be >4 g/kg/day for both male and female rats, under the experimental conditions of this study.